Gender-Based Violence and State Response: Assessing the Implementation of the TPKS Law (Contemporary Issues on Indonesian Human Rights Law and Policy, 2025)
This paper evaluates the implementation of Indonesia’s 2022 Law on the Elimination of Sexual Violence (TPKS Law), which aims to address gender-based violence (GBV) and provide stronger legal protections for survivors. While the law marks a significant step toward gender justice, its effectiveness in practice remains debated. The study assesses the law’s provisions, such as the creation of special courts for sexual violence cases and the provision of victim protection mechanisms. By analyzing case studies, interviews with legal professionals, and survivors, the paper explores the challenges in implementation, including gaps in institutional capacity, cultural barriers, and a lack of public awareness. Furthermore, the research investigates how local governments, NGOs, and grassroots organizations are contributing to the law’s enforcement. The findings suggest that while the law’s enactment was a milestone, its success hinges on overcoming challenges such as victim-blaming, inconsistent legal interpretations, and limited support for survivors. The paper concludes by offering recommendations for strengthening the law’s implementation, such as improving training for law enforcement, increasing community outreach, and promoting comprehensive victim support services.